Chronic heavy alcohol consumption impairs the ability of demineralized allogenic bone matrix to support osteoinduction in alcohol-naïve rats - Russell T. Turner; Amida F. Kuah; Cynthia H. Trevisiol; Kathy S. Howe; Adam J. Branscum; Urszula T. Iwaniec (Bone Reports)
Allografts play an important role in treatment of complex bone fractures and deformities. The purpose of this study was to test the hypothesis that alcohol consumption impairs graft incorporation and bone healing by two mechanisms: (1) by lowering osteoinductive capacity and (2) by suppressing bone formation. We performed experiments using a demineralized allogeneic bone matrix (DBM) model in which DBM harvested from donor rats fed control or ethanol diet was implanted subcutaneously into recipient rats fed control or ethanol diet. We also evaluated the efficacy of intermittent parathyroid hormone (PTH) on bone graft incorporation (DBM from donor rats fed alcohol or control diet) using a critical size defect model. Bone formed during osteoinduction was measured by micro-computed tomography. Experiment 1: Bone volume was lower in DBM harvested from ethanol-consuming donors 6 weeks following implantation into recipients fed control diet, indicating that exposure of the donor rats to ethanol lowered osteoinductive capacity. Experiment 2: Bone volume was lower in DBM harvested 3 weeks following implantation from ethanol-consuming donors into ethanol-consuming recipients compared to DBM harvested from control donors implanted into control recipients or DBM harvested from control donors implanted into ethanol-consuming recipients. Experiment 3: Ethanol consumption by donors resulted in a tendency for lower DBM bone volume (p = 0.085) whereas PTH treatment resulted in higher DBM bone volume in the critical size defect model. Our results suggest that chronic heavy alcohol consumption by allograft donors may impair osteoinduction and this negative outcome may be worsened by alcohol intake during bone healing. Additionally, PTH has the potential to increase osteoinduction in DBM harvested from both abstinent and alcohol-consuming donors.